INOVASI ATMOSFER TERKENDALI: PEMELIHARAAN KESEGARAN BUAH PISANG UNTUK PENINGKATAN KETERSEDIAAN DAN KUALITAS KONSUMSI - Imansyah, Fitri (Universitas Mataram, 2024)
Bananas are a climacteric fruit, where the banana will continue the ripening process even though it has been harvested and is followed by a damage process because the fruit continues to carry out respiration and metabolism processes. The respiration process in the fruit will cause the fruit to ripen quickly and become overripe. This is one of the obstacles in maintaining the shelf life of bananas. The rotting time of fruit can be controlled by adding or subtracting gas so that O2 and CO2 can be adjusted to obtain various gas compositions. Food preservation technology such as Modified Atmosphere Storage (MAS) is a system for controlling air flow rates to reduce O2 levels by injecting CO2 to prevent the rate of rotting in fruit. Innovations in controlled atmosphere storage technology (IAT) have become the main focus in efforts to increase the availability and quality of banana consumption. This activity aims to evaluate the implementation of IAT in banana cultivation and its impact on supply availability and consumer preferences. The activity method involves controlling the temperature, humidity, and gas composition around the banana fruit during the storage and distribution process. The results of the activity show that the application of IAT is effective in maintaining the freshness of bananas by inhibiting the ripening process and reducing the level of post-harvest damage. Increasing the shelf life of bananas provides significant flexibility in the supply chain, optimizing distribution and reducing waste. In addition, consumer surveys show that bananas stored using this technology are preferred because of their better quality. In the context of agricultural sustainability, this activity also illustrates IAT's contribution in creating a more sustainable agricultural model through waste reduction and distribution efficiency. Although there are several challenges such as implementation costs and understanding of the technology by farmers, the long-term positive potential of implementing IAT in banana cultivation is clear.